Intracellular localization of viral polypeptides during simian virus 40 infection. - Kasamatsu, H (1979)
African green monkey kidney cells infected by simian virus 40 were analyzed by immunofluorescence techniques for the nature and the time course of the appearance of viral polypeptides during infection. Reagents used in the study were anti-Vpl sera and affinity-purified anti-Vpl immunoglobulin G, anti-Vp3 sera, antivirus (anti-V) sera, and anti-tumor antigen sera. The results are summarized as follows. (i) Three types of staining, nuclear, perinuclear, and perinuclear accompanied by cytoplasmic staining, were observed in infected cells in reaction with anti-vpl antibody. In addition, a highly structured staining was observed at the periphery of nuclei of infected cells late in infection. (ii) In reaction with anti-Vp3 serum, the staining was confined within nuclei of cells throughout infection. (iii) Vp1 and Vp3 antigens seem to occupy different spacial regions of the nuclear area in cells. (iv) Vp1 and Vp3 antigens were expressed simultaneously during infection. (v) Centriolar staining observed early in infection paralleled the appearance of tumor (T-) antigen until 24 h after infection, after which time the frequency of positive centriolar staining decreased as infection progressed. (vi) T-antigen was first expressed at about 8 h after infection, and Vp1 and Vp3 antigens were first expressed at about 20 h after infection.